Regional and Spatial Development of Medium-Sized Municipalities in the North Central Region - Dokova, Sonia; Petrov, Kamen; Tsonkov, Nikolai; Nikolov, Georgi; Tzolov, Georgi; Vasileva, Elka; Tanakov, Nikola; Berberova–Valcheva, Cvetelina (Research Papers, 2019)
Reducing of number of city functions and slow urban development of medium and small cities among 30000 – 100000 people (which are research object) create terms of social economic disproportions. In this situation the main purpose of the research is analyzing the tendencies and regional development potential of medium size cities in North central region in Bulgaria. For the need of methodology, the authors use quantitative and qualitative methods as method of hidden internal dependencies between surveying objects; methods for detection of cause – effect relations between objects and phenomenon; comparison method; analysis and synthesis.Research task: To analyze social economic situation in medium size cities in North central Bulgarian region; The authors are going to realize systematic estimation of regional development instruments contribution, effectiveness and effects of strategy and regional and local plans for development related to regional development of surveying cities in the region; To formulate final conclusions on basis of municipalities analysis.In comparison to other regions in Bulgaria there are great misbalances. The tendencies and perspectives for their development illustrates realism and fulfilment of planning steps, activities and concrete projects in accordance to rehabilitate infrastructure – technical, educational, social and cultural.